Reading habits and interests of selected Rizal High School students - Ramos, Guizzelle S. (2011)
This study is about the reading habits and interest on fiction books of selected Rizal High School (Main) students. It aims to know if there are any similarities in the interests of first year to fourth year students, or lack thereof. It also want to find out the factors that affect the reading habits and interest of the students. With this, suggestions and recommendation were made to improve the collection and services on the fiction books of the school.